HUBUNGAN INTENSITAS SHOLAT TAHAJUD DENGAN TEKANAN DARAH - Diyono Diyono; Siyam Khotimah Musnidawati (KOSALA : Jurnal Ilmu Kesehatan, 2018)
Background and Objectives: The prevalence of hypertension in Indonesia reaches31.7%. In developing countries including Indonesia, deaths from hypertension and itscomplications reach 80%. In addition, about 54% of stroke and 47% of heart disease inthe world caused by hypertension. Although pharmacological and non-pharmacologicalhypertension management efforts have been done, but the incidence of hypertension andits complications tend to increase, so there is a need to research for more therapeuticalternatives. The purpose of this study was to determine the effect of tahajud prayertherapy on blood pressure in hypertensive clients.Methods and Subjects Research: Quasy Experiment research with one group pre testpost test design. Subject of research 28 respondents taken by simple random sampling.Results: (1) The highest percentage of hypertension is moderate hypertension categorythat reaches 60.7% (2) Majority or 85.7%, hypertensive patients do not perform treatmentor management well and regularly.Conclusion: tahajud prayer significantly influences as a therapy to lower blood pressure.Keywords: Hypertension, TahajudÂ